Null mutation in PGAP1 impairing Gpi-anchor maturation in patients with intellectual disability and encephalopathy. - Yoshiko Murakami; Hasan Tawamie; Yusuke Maeda; Christian Büttner; Rebecca Buchert; Farah Radwan; Stefanie Schaffer; Heinrich Sticht; Michael Aigner; André Reis; Taroh Kinoshita; Rami Abou Jamra (PLoS Genetics)
Many eukaryotic cell-surface proteins are anchored to the membrane via glycosylphosphatidylinositol (GPI). There are at least 26 genes involved in biosynthesis and remodeling of GPI anchors. Hypomorphic coding mutations in seven of these genes have been reported to cause decreased expression of GPI anchored proteins (GPI-APs) on the cell surface and to cause autosomal-recessive forms of intellectual disability (ARID). We performed homozygosity mapping and exome sequencing in a family with encephalopathy and non-specific ARID and identified a homozygous 3 bp deletion (p.Leu197del) in the GPI remodeling gene PGAP1. PGAP1 was not described in association with a human phenotype before. PGAP1 is a deacylase that removes an acyl-chain from the inositol of GPI anchors in the endoplasmic reticulum immediately after attachment of GPI to proteins. In silico prediction and molecular modeling strongly suggested a pathogenic effect of the identified deletion. The expression levels of GPI-APs on B lymphoblastoid cells derived from an affected person were normal. However, when those cells were incubated with phosphatidylinositol-specific phospholipase C (PI-PLC), GPI-APs were cleaved and released from B lymphoblastoid cells from healthy individuals whereas GPI-APs on the cells from the affected person were totally resistant. Transfection with wild type PGAP1 cDNA restored the PI-PLC sensitivity. These results indicate that GPI-APs were expressed with abnormal GPI structure due to a null mutation in the remodeling gene PGAP1. Our results add PGAP1 to the growing list of GPI abnormalities and indicate that not only the cell surface expression levels of GPI-APs but also the fine structure of GPI-anchors is important for the normal neurological development.